The search for sunken treasure - Stilton, Geronimo; Keys, Larry; Mirellik (New York : Scholastic, 2006)
Geronimo Stilton, publisher of "The Rodent's Gazette" in New Mouse City, travels with his friends to the Ratlapagos Islands in search of treasure, and soon begin to suspect they are not the only ones involved in the quest.
Translation of: El mistero del tesoro scomparso.
"#25"--Spine.
3.6.
3-6.
540L
O
Keywords: Stilton, Geronimo -- Juvenile fiction; Stilton, Geronimo -- Fiction; Mice -- Juvenile fiction; Journalists -- Juvenile fiction; Diving -- Juvenile fiction; Treasure troves -- Juvenile fiction; Mice -- Fiction; Journalists -- Fiction; Diving -- Fiction; Buried treasure -- Fiction; Voyages and travels -- Fiction; Adventure and adventurers -- Fiction; Detective and mystery fiction; Action and adventure fiction